CD99 ligation induces intercellular cell adhesion molecule-1 expression and secretion in human gingival fibroblasts - Suttichai Krisanaprakornkit (2018)
Objective: To examine CD99 expression and its functional role in ICAM-1 induction in human gingival fibroblasts (HGFs) and human gingival epithelial cells (HGECs) by activating cells with anti-CD99 monoclonal antibody, MT99/3. Background: Engagement of CD99 with agonistic antibodies has been shown to regulate immune responses, cell adhesion and migration, and cell death in several studies. Particularly, this engagement results in transendothelial migration of leukocytes mediated by intercellular adhesion molecule-1 (ICAM-1) induction in endothelial cells. Methods: Total mRNA and protein were isolated from HGFs and HGECs for analyses of CD99 and ICAM-1 expression. Surface expression of CD99 and ICAM-1 was analysed by flow cytometry, and the detection of soluble ICAM-1 was assayed by immunoprecipitation and ELISA. Results: CD99 surface expression was constitutive on HGFs to a greater extent than that on HGECs. CD99 ligation with MT99/3 induced ICAM-1 mRNA expression in HGFs, but not in HGECs. Interestingly, CD99 ligation led to an increased level of soluble ICAM-1 detected in culture supernatant, whereas interleukin-1β (IL-1β) treatment induced expression of membrane-bound ICAM-1. Furthermore, ICAM-1 induction by CD99 engagement was demonstrated to involve the activation of the p50 subunit of nuclear factor-kappaB (NF-κB), extracellular signal-regulated kinase, and p46 c-Jun N-terminal kinase that differed from that by IL-1β treatment. Conclusion: Our study has shown the involvement of CD99 ligation in the up-regulation of ICAM-1 expression and its secretion in gingival fibroblasts, which may be essential for better understanding of the pathogenesis of periodontal disease. © 2012 Elsevier Ltd.